Effect of light intensity, temperature and diet on reproduction of Hirudinea sp. - Zulhisyam Abdul Kari @ Abdullah; Ahmad Anwar Mohamed Ismail; Ibrahim Che Omar (2010)
Leeches (Phylum: Annelida, Class: Hirudinea) are widely distributed all over the world in various habitats, such as freshwater, seas, desert, and oases (Gouda, 2006). In this study, the effect of light intensity, temperature and diet on the reproductive efficiency of Hirudinea sp. was examined with eight different conditions with condition 1 (temperature: 25-28°C, light intensity: 0 lx, diet: fresh eel blood), condition 2 (temperature: 30-32°C, light intensity: 0 lx, diet: fresh eel blood), condition 3 (temperature: 30-32°C, light intensity: 100-150 lx, diet: fresh eel blood), condition 4 (temperature: 25-28°C, light intensity: 100-150 lx, diet: fresh eel blood), condition 5 (temperature: 30-32°C, light intensity: 100-150 lx, diet: booster), condition 6 (temperature: 25-28°C, light intensity: 100-150 lx, diet: booster), condition 7 (temperature: 25-28°C, light intensity: 0 lx, diet: booster) and condition 8 (temperature: 30-32°C, light intensity: 0 lx, diet: booster). After 3 months of culture, the number of cocoons produced was very significantly different among the different conditions (p=0.00). The average number of hatchlings per cocoon was significantly different (p ≤ 0.05) where condition 1 gave the highest number with mean and standard deviation of 6.23±0.25, but hatching rate was not (p=0.354). The condition 5 produced the highest mortality of parent leeches with mean and standard deviation of 52±13.86%. The size of the cocoons were not significantly different among the treatments, with the condition 1 having the largest cocoon size with the means and standard deviations of 22.19±0.92mm and 13.26±0.07mm according to their length and diameter, respectively. The wet weight of cocoons was significantly different (p ≤ 0.05) with the condition 1 producing the heaviest with the mean and standard deviation of 1.26±0.11g compared to condition 5 the lightest with mean and standard deviation of 0.22±0.38g.